Investigating the Determinants of IoT Wearable Technology Usage - Suhluli, Salem (Curtin University, 2023)
This research investigates the determinants of wearable technology adoption, and explores users’ perceptions of privacy and security in the context of wearable technology. Using a mixed method approach the findings yielded several theoretical and practical contributions. This research provides a comprehensive tested and validated model of the determinants of wearables adoption. The distinctive features of this model are the incorporation of conventional IS constructs and associated pervasive and wearables adoption factors.